"No war, no peace" in a region in flux: crisis, escalation, and possibility in the Eritrea-Ethiopia rivalry. Issue 3 (3rd July 2018) - Woldemariam, Michael
ABSTRACT: This article examines the evolving rivalry between Eritrea and Ethiopia in light of military clashes between the two countries that occurred in June 2016. Drawing on rationalist understandings of international politics, it illustrates the calculus that sustained the rivalry for nearly 16 years. These forces, while sufficient to have maintained the situation of "no war, no peace" for a considerable period of time, gave way to a new set of dynamics that significantly eroded the fragile status quo. In that context, a slow, but perceptible shift in the regional balance power seemed to have increased the risk of another round of military conflict between Eritrea and Ethiopia. While Ethiopia's recent selection of a new prime minister has created real possibility of a reset of Eritrea-Ethiopia relations, the underlying structural dynamics between the two countries remain volatile. For better or worse, Africa's most intractable interstate rivalry sits at a critical juncture.